Which Diet for Calcium Stone Patients: A Real-World Approach to Preventive Care - D’Alessandro, Claudia (Nutrients, 2019)
Kidney stone disease should be viewed as a systemic disorder, associated with or predictive of hypertension, insulin resistance, chronic kidney disease and cardiovascular damage. Dietary and lifestyle changes represent an important strategy for the prevention of kidney stone recurrences and cardiovascular damage. A full screening of risk factors for kidney stones and for cardiovascular damage should be recommended in all cases of calcium kidney stone disease, yet it is rarely performed outside of stone specialist clinics. Many patients have a history of kidney stone disease while lacking a satisfactory metabolic profile. Nonetheless, in a real-world clinical practice a rational management of kidney stone patients is still possible. Different scenarios, with different types of dietary approaches based on diagnosis accuracy level can be envisaged. The aim of this review is to give patient-tailored dietary suggestions whatever the level of clinical and biochemistry evaluation. This can help to deliver a useful recommendation, while avoiding excessive dietary restrictions especially when they are not based on a specific diagnosis, and therefore potentially useless or even harmful. We focused our attention on calcium stones and the different scenarios we may find in the daily clinical practice, including the case of patients who reported renal colic episodes and/or passed stones with no information on stone composition, urinary risk factors or metabolic cardiovascular risk factors; or the case of patients with partial and incomplete information; or the case of patients with full information on stone composition, urinary risk factors and metabolic cardiovascular profile.